Solubility enhancement of mefenamic acid by inclusion complex with β-cyclodextrin: in silico modelling, formulation, characterisation, and in vitro studies - Dounia Sid; Milad Baitiche; Zineb Elbahri; Ferhat Djerboua; Mokhtar Boutahala; Zouhair Bouaziz; Marc Le Borgne (Taylor & Francis Group, 2021)
The aim of this study was to prepare and characterise inclusion complexes of a low water-soluble drug, mefenamic acid (MA), with β-cyclodextrin (β-CD). First, the phase solubility diagram of MA in β-CD was drawn from 0 to 21 × 10−3 M of β-CD concentration. A job's plot experiment was used to determine the stoichiometry of the MA:β-CD complex (2:1). The stability of this complex was confirmed by molecular modelling simulation. Three methods, namely solvent co-evaporation (CE), kneading (KN), and physical mixture (PM), were used to prepare the (2:1) MA:β-CD complexes. All complexes were fully characterised. The drug dissolution tests were established in simulated liquid gastric and the MA water solubility at pH 1.2 from complexes was significantly improved. The mechanism of MA released from the β-CD complexes was illustrated through a mathematical treatment. Finally, two in vitro experiments confirmed the interest to use a (2:1) MA:β-CD complex.